Protecting Our Most Vulnerable: Why Antimicrobial Stewardship for Senior Living Is a Must: Results from Four Large Senior Living Centers. (4th October 2017) - Guharoy, Roy; Vann, Rita; Miller, Suzanne; Groves, Clariecia; Sturm, Lisa; O'Neil, Kevin; Hendrich, Ann; Fakih, Mohamad
Abstract: Background: Antibiotics are frequently prescribed among senior living residents, with the over diagnosis of infections playing a significant problem. Elderly are vulnerable to the harms of inappropriate antibiotic use. Methods: We evaluated the use of systemic antibiotics, the diagnosis of facility-onset urinary tract infection (based on McGeer's criteria), and C. difficile infections in the 4 large (>250 resident beds) Senior Living Centers in 4 different states. All measures were normalized per 1, 000 resident-days and evaluated over 9 months between July 2015 and March 2016. In addition, we visited the 4 facilities and qualitatively evaluated factors that may influence antibiotic use. Results: There were 27, 255 antibiotic-days at a rate of 106.8 per 1, 000 resident-days. Non-quinolone antiurinary agents accounted for 22.3 (20.9%), quinolones for 21.5 (20.2%), cephalosporins 16.8 (15.7%), penicillins 8.0 (7.5%), and tetracyclines 8.2 (7.7%), and macrolides 6.31 (5.9%) antibiotic-days per 1, 000 resident-days. There were marked differences in the use of urinary antimicrobials between the 4 facilities (Figure 1). Facility A and B had more than 6 times antibiotic use compared with facility D, and had the highest rates for UTI (Table 1). Clostridium difficile infections were highest in facility A compared with other facilities. The two facilities lowest antimicrobial use had strong physician-nursing partnership with engaged medical directors. Conclusion: Considerable opportunities reside in Senior Living to optimize testing and appropriate antibiotic use. Engaging both nurses and physicians, in addition to regular evaluation of use with feedback are key to standardizing the care and improving the outcomes. Disclosures: All authors: No reported disclosures.